Reduced plasma adiponectin levels relative to oxidized low density lipoprotein and nitric oxide in coronary artery disease patients (Clinics, 2011)
INTRODUCTION: Adiponectin is a circulating hormone that is produced exclusively by adipocytes and has antiinflammatory and anti-atherogenic properties. The hypothesis that there are differences in adiponectin levels between stable and unstable coronary-artery disease patients remains controversial. Furthermore, the potential relationships between the plasma adiponectin level and the inflammatory and non-inflammatory markers (oxidized low density lipoprotein and nitric oxide) in patients with stable and unstable coronary-artery disease relative to normal subjects have not been assessed. OBJECTIVES: To assess whether plasma adiponectin levels differ among patients with stable and unstable coronary-artery disease and among control subjects, and to correlate plasma adiponectin level with inflammatory and clinical risk factors (such as oxidized-LDL and nitric oxide) in these patients. METHODS: This study included 50 control subjects, 50 stable angina patients and 50 unstable angina patients with angiographically documented coronary-artery disease. Plasma adiponectin and oxidized-LDL levels were determined using an enzyme immunoassay. Plasma nitric oxide, high sensitivity C-reactive protein and lipid profile levels were also measured. RESULTS: Plasma adiponectin levels were lower in the unstable angina patients (4.9 ± 1.30 µg/mL) than in the stable angina patients (6.34 ± 1.0 µg/mL) or in the controls (9.25 ± 1.8 µg/mL); these levels were also significantly lower in stable angina patients versus controls (p